Mix design method for self compacting metakaolin concrete with different properties of coarse aggregate - Khaleel, O.R.; Razak, Hashim Abdul (Elsevier, 2014)
This study deals with a proposed mix design method for SCC utilizing different properties of coarse aggregate. The work was conducted in three phases, i.e. paste, mortar and concrete to facilitate the mix design process. Initial investigation on cement paste determined the basis for water cement ratio and superplasticizer dosage for the concrete. For the study on mortar, metakaolin (MK) as pozzolan was used at replacement levels of 5, 10, 15, and 20 by weight of cement. Self compactability of mortars was obtained by adding suitable materials such as mineral admixtures and superplasticizer which provided a sufficient balance between flowability and viscosity of the mix. The optimum MK replacement level for cement was 10 from the viewpoint of workability and strength. Flowability of mortar decreased with the use of metakaolin. Moreover, strength of mortar increased when the optimum replacement level of pozzolan was used. Different fresh concrete tests were adopted. The results obtained for fresh concrete properties showed that flowability of concrete increased with increase flowability of mortar. The mixes which contained coarse aggregate with lower volume, small size, and continuous grading affected positively the fresh properties of SCC. Finally, the mix design method used was successful in producing SCC with different coarse aggregate properties. Â© 2013 Elsevier Ltd.